Application of Molecular Docking for the Development of Improved HIV-1 Reverse Transcriptase Inhibitors - Soltani, Arash; Hashemy, Seyed Isaac; Avval, Farnaz Zahedi; Rafatpanah, Houshang; Rezaee, Seyed Abdolrahim; Griffith, Renate; Mashkani, Baratali (Current computer-aided drug design, 2021)
Inhibition of the reverse transcriptase (RT) enzyme of the human immunodeficiency virus (HIV) by low molecular weight inhibitors is still an active area of research. Here, protein-ligand interactions and possible binding modes of novel compounds with the HIV-1 RT binding pocket (the wild-type as well as Y181C and K103N mutants) were obtained and discussed. A molecular fragment-based approach using FDA-approved drugs were followed to design novel chemical derivatives using delavirdine, efavirenz, etravirine and rilpivirine as the scaffolds. The drug-likeliness of the derivatives was evaluated using Swiss-ADME. The parent molecule and derivatives were then docked into the binding pocket of related crystal structures (PDB ID: 4G1Q, 1IKW, 1KLM and 3MEC). Genetic Optimization for Ligand Docking (GOLD) Suite 5.2.2 software was used for docking and the results analyzed in the Discovery Studio Visualizer 4. A derivative was chosen for further analysis, if it passed drug-likeliness and the docked energy was more favorable than that of its parent molecule. Out of the fifty-seven derivatives, forty-eight failed in drug-likeness screening by Swiss-ADME or at the docking stage. The final results showed that the selected compounds had higher predicted binding affinities than their parent scaffolds in both wild-type and the mutants. Binding energy improvement was higher for the structures designed based on second-generation NNRTIs (etravirine and rilpivirine) than the first-generation NNRTIs (delavirdine and efavirenz). For example, while the docked energy for rilpivirine was -51 KJ/mol, it was improved for its derivatives RPV01 and RPV15 up to - 58.3 and -54.5 KJ/mol, respectively. In this study, we have identified and proposed some novel molecules with improved binding capacity for HIV RT using a fragment-based approach.